2005
DOI: 10.1002/elps.200410087
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sheathless and sheath‐flow electrospray interfaces for the capillary electrophoresis‐electrospray ionization‐mass spectrometry analysis of peptides

Abstract: Comparison of sheathless and sheath-flow electrospray interfaces for the capillary electrophoresis-electrospray ionization-mass spectrometry analysis of peptidesCapillary electrophoresis coupled to mass spectrometry via an electrospray interface provides a powerful system for separation and characterization of a high number of biomolecules. The present paper describes a home-made sheathless interface and compares it with a commercial sheath-flow interface, using a separation method based on a peptide hormone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 25 publications
2
43
2
Order By: Relevance
“…ESI is the method of choice for producing gas phase ions from solution because it is a very soft ionization method and is useful for the ionization of larger molecules or biomolecules. ESI-MS can be used for the analysis of complex mixtures [1][2][3][4][5] and is commonly used to couple separation techniques, such as high performance liquid chromatography (HPLC) [6][7][8][9], capillary electrophoresis (CE) [10][11][12][13][14][15][16][17][18][19][20][21], or microchannel electrophoresis (ME) [22][23][24][25][26][27][28][29] with MS. Many sample introduction methods, particularly those that employ separations, rely on pressure driven flow for sample introduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ESI is the method of choice for producing gas phase ions from solution because it is a very soft ionization method and is useful for the ionization of larger molecules or biomolecules. ESI-MS can be used for the analysis of complex mixtures [1][2][3][4][5] and is commonly used to couple separation techniques, such as high performance liquid chromatography (HPLC) [6][7][8][9], capillary electrophoresis (CE) [10][11][12][13][14][15][16][17][18][19][20][21], or microchannel electrophoresis (ME) [22][23][24][25][26][27][28][29] with MS. Many sample introduction methods, particularly those that employ separations, rely on pressure driven flow for sample introduction.…”
Section: Introductionmentioning
confidence: 99%
“…For optimal sample utilization, determination of the parameters that provide the highest signal intensity is crucial. Many previous studies have been performed to optimize different parameters that affect the ESI signal, like sheath flow [10,12,20], nebulizing gas [13,16], buffer systems [20,30], and ESI voltage [31,32]. Likewise, ESI emitters have been extensively studied because the characteristics of the emitter, such as the emitter i.d., the surface area of the emitter orifice, and the hydrophobicity, have a great impact on the observed ESI signal; in addition to influencing the working parameters of the system, such as flow rate or ESI voltage [33].…”
Section: Introductionmentioning
confidence: 99%
“…This fact was clearly demonstrated by Sanz-Nebot et al [34]. A comparison between a sheathless interface based on a graphite coated tip and a sheath flow interface revealed that the reproducibility found with the sheathless interface was, by far, lower than that determined using the sheath flow interface, while the LOD values were similar [34]. Moreover, the formation of the spray in these sheathless devices is directly related to the presence of a strong EOF, which in many cases can reduce spray stability or, directly, to preclude its application.…”
Section: Sheathless Interfacementioning
confidence: 53%
“…However, although this kind of interface is in general more sensitive than the sheath flow interface, the problems related to the manufacturing of these sheathless devices, together with their low robustness and reproducibility have to be also considered. This fact was clearly demonstrated by Sanz-Nebot et al [34]. A comparison between a sheathless interface based on a graphite coated tip and a sheath flow interface revealed that the reproducibility found with the sheathless interface was, by far, lower than that determined using the sheath flow interface, while the LOD values were similar [34].…”
Section: Sheathless Interfacementioning
confidence: 82%
“…Over the past decade, the usefulness, versatility and robustness of this interface has been demonstrated in various application areas [2,4,6,12,22,34]. Typical limits of detection (LODs), without usage of preconcentration methods, are often in the order of 1 µM in sample concentration (depending on the MS method used) [9,11,[35][36][37]. The co-axial sheath-liquid interface design, however, compromises sensitivity since the combined EOF and sheath-liquid flow is high compared with flow-rates used, e.g., in nanoflow HPLC and thus lack the sensitivity enhancement occurring in nano-ESI.…”
Section: Requirements For Ce-esi-ms Interfacingmentioning
confidence: 99%